2018
DOI: 10.1101/350652
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Histone H3-H4 Tetramer is a Copper Reductase Enzyme

Abstract: 28Ancestral histones were present in organisms with small genomes, no nucleus and little 29 ability for epigenetic regulation, suggesting histones may have an additional, unknown function. 30We report that the histone H3-H4 tetramer is an enzyme that catalyzes the reduction of Cu 2+ to

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
0
13
2
Order By: Relevance
“…Copper ions are known to bind with protein Atox1 in nucleus to regulate gene transcription in vertebrates, 44 and directly activate Cup2 transcriptional activities and suppress Mac1 transcriptional activities in eukaryotes. 45 However, the data in this study failed to provide the solid evidence that Cu ions suppress transcriptional activities of SRF and Myog on smyd1b directly or indirectly. Additionally, it is still unclear which Cu chaperone protein in nucleus mediates Cu ions in suppressing the transcriptional activity of SRF and Myog on smyd1b gene.…”
Section: Cu Ions May Inhibit Myofibrillogenesis Via Downregulating Sm...contrasting
confidence: 67%
“…Copper ions are known to bind with protein Atox1 in nucleus to regulate gene transcription in vertebrates, 44 and directly activate Cup2 transcriptional activities and suppress Mac1 transcriptional activities in eukaryotes. 45 However, the data in this study failed to provide the solid evidence that Cu ions suppress transcriptional activities of SRF and Myog on smyd1b directly or indirectly. Additionally, it is still unclear which Cu chaperone protein in nucleus mediates Cu ions in suppressing the transcriptional activity of SRF and Myog on smyd1b gene.…”
Section: Cu Ions May Inhibit Myofibrillogenesis Via Downregulating Sm...contrasting
confidence: 67%
“…Still, as the number of metabolites that can modify histones keeps on growing, e.g., with the recent addition of lactylation (Zhang et al , 2019), an even more complex language starts to surface. For example, histones can also sense cellular metal content (Attar et al , 2020) or become dopaminylated and serotinylated in the brain (Lepack et al , 2020), mediating drug addiction and depression. Yet, while trying to understand the function of so many different hPTMs is challenging in its own right, trying to grasp the emerging complexity of their interplay, i.e., the histone code, is simply overwhelming.…”
Section: Figure Trypsin‐mediated Histone H4 Clipping During Enterocyt...mentioning
confidence: 99%
“…The Cu-Zn superoxide dismutase, Sod1, is a major contributor to antioxidant defense and is likely to protect Fe-S clusters from damage in the presence of oxygen (51). We previously found that H3H113N diminishes Sod1 activity (24). However, in the unique context of YFH1-off and the resulting decrease of Fe-S clusters, we considered whether the restoration of function by H3H113N depended on Sod1.…”
Section: H3h113n When Fe-s Cluster Assembly Is Disruptedmentioning
confidence: 99%